PATIENT COMPLIANCE IN CHRONIC DISEASE MANAGEMENT PROGRAMS BASED ON THE HEALTH BELIEF MODEL HOLISTIC NURSING APPROACH IN BANTUL - Widarto, Widarto; Joko Prasetyo; Anggraeni, Novita Anna (Universitas Kadiri, 2025)
The Chronic Disease Management Program (Prolanis) is a systematic strategy aimed at improving the quality of life for patients with chronic illnesses such as hypertension and diabetes mellitus. However, patient adherence to this program remains relatively low, particularly in semi-rural areas such as the Dlingo II Primary Health Center, Bantul. Understanding the factors that influence adherence is crucial for designing more effective and contextually appropriate interventions. This study aims to analyze the determinants of patient adherence to Prolanis using the Health Belief Model (HBM) framework and interpret the findings through a holistic nursing perspective. A quantitative approach with a cross-sectional design was employed, involving 163 active Prolanis patients within the working area of Dlingo II Primary Health Center. The variables examined included perceived benefits, perceived barriers, social support, and cues to action, analyzed using bivariate chi-square tests and multivariate binary logistic regression. The results indicate that all variables within the HBM framework significantly influence patient adherence (p < 0.05), with cues to action being the most dominant factor (OR = 8.615), followed by perceived benefits (OR = 5.637), social support (OR = 5.026), and perceived barriers (OR = 2.878). These findings highlight the importance of contextual education, meaningful reminders, and supportive social environments as key factors for program success. Adherence to Prolanis is influenced not only by individual perceptions but also by social dynamics and local cultural values. Integrating the HBM approach with holistic nursing provides a more comprehensive understanding of patient behavior and supports the effectiveness of community-based interventions in semi rural settings.